Polysaccharide Degradation by the Intestinal Microbiota and Its Influence on Human Health and Disease. Issue 16 (14th August 2016) - Cockburn, Darrell W.; Koropatkin, Nicole M.
Abstract: Carbohydrates comprise a large fraction of the typical diet, yet humans are only able to directly process some types of starch and simple sugars. The remainder transits the large intestine where it becomes food for the commensal bacterial community. This is an environment of not only intense competition but also impressive cooperation for available glycans, as these bacteria work to maximize their energy harvest from these carbohydrates during their limited transit time through the gut. The species within the gut microbiota use a variety of strategies to process and scavenge both dietary and host-produced glycans such as mucins. Some act as generalists that are able to degrade a wide range of polysaccharides, while others are specialists that are only able to target a few select glycans. All are members of a metabolic network where substantial cross-feeding takes place, as by-products of one organism serve as important resources for another. Much of this metabolic activity influences host physiology, as secondary metabolites and fermentation end products are absorbed either by the epithelial layer or by transit via the portal vein to the liver where they can have additional effects. These microbially derived compounds influence cell proliferation and apoptosis, modulate the immune response, and can alter host metabolism. This review summarizes the molecular underpinnings of these polysaccharide degradation processes, their impact on human health, and how we can manipulate them through the use of prebiotics. Graphical Abstract: Highlights: Commensal gut bacteria (microbiota) have an extensive capacity to utilize carbohydrates from their environment including both dietary polysaccharides (fiber) and endogenous glycans such as those that decorate the host mucosal layer. The glycan utilization strategies employed by dominant gut bacterial phyla, the Bacteroidetes and Firmicutes, are distinct although both involve cell surface processing of a large glycan prior to cellular import. The Bacteroidetes utilize multi-protein complexes in which carbohydrate binding and processing is provided by different polypeptides that work with a TonB-dependent receptor, whereas many Firmicutes express large polypeptides composed of both carbohydrate-binding and catalytic functions and release oligosaccharides for capture by a distinct importer. The bacteria in the gut exist in a series of cross-feeding networks where metabolites are exchanged, with keystone species acting as critical nodes. Mucin localization and metabolism by gut bacteria is largely beneficial to the host, as it may help stabilize the gut community and promote mucin secretion and barrier function. Prebiotics are functional foods, typically oligosaccharides, that promote proliferation of beneficial gut species that have evolved a variety of mechanisms to efficiently scavenge these glycans.